Ashmolean Museum. Report of the Visitors 1957 (Accessions during the year) - Anonymus, A.
p. 1 (pl. I b-d: Ivories from Nimrud; II a-f: Pieces of ivory inlay); p. 16-17: Objects from the excavations at Jericho.